2020
DOI: 10.1177/1078155220905648
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review: Role of systemic therapy on treatment and prevention of brain metastasis in renal cell carcinoma

Abstract: Aim To define the inclusion/exclusion status of patients with brain metastasis in phase-III clinical trials and the effect of systemic therapies in metastatic renal cell cancer patients with brain metastasis. Methods “kidney neoplasms”[MeSH Terms] OR (“kidney”[All Fields] AND “neoplasms”[All Fields]) OR “kidney neoplasms”[All Fields] OR (“kidney”[All Fields] AND “cancer”[All Fields]) OR “kidney cancer”[All Fields] AND “brain metastasis” were used for searching “PubMed” electronic database and “clinicaltrials.g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“… 46 , 47 , 48 In our previous case-report, we observed that nivolumab within the last seven days before diagnosis provided a good clinical course of COVID-19 in a seventy-five-year-old female malign melanoma patient. 49 Furthermore, there are still ongoing clinical trials investigating the effect of nivolumab on COVID-19 (NCT04413838, NCT04343144, NCT04356508). One of the main concerns regarding the use of ICIs during pandemic is that the clinical findings of pneumonitis due to ICIs or pneumonia of COVID-19 may confuse the patient management.…”
Section: Discussionmentioning
confidence: 99%
“… 46 , 47 , 48 In our previous case-report, we observed that nivolumab within the last seven days before diagnosis provided a good clinical course of COVID-19 in a seventy-five-year-old female malign melanoma patient. 49 Furthermore, there are still ongoing clinical trials investigating the effect of nivolumab on COVID-19 (NCT04413838, NCT04343144, NCT04356508). One of the main concerns regarding the use of ICIs during pandemic is that the clinical findings of pneumonitis due to ICIs or pneumonia of COVID-19 may confuse the patient management.…”
Section: Discussionmentioning
confidence: 99%
“…A systemic review and meta-analysis of COVID-19 patients with cancer who were treated with chemotherapy found that there was an increased risk of death (OR: 1.9; 95% confidence interval: 1.3–2.7), after adjusting for confounding variables, compared to patients that received targeted therapies, IMT, surgery or radiotherapy [ 49 ]. Another meta-analysis of 6042 patients with COVID-19 showed that ICIs received within 30 days before diagnosis did not increase mortality or the severity of disease in affected patients [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mainstay of treatment for brain metastasis from RCC is stereotaxic radiosurgery with or without tumor resection, depending on the size and location of the lesion. There is a lack of evidence with regard to which systemic therapies are best suited for this patient population, but anti-vascular endothelial growth factor tyrosine kinase inhibitors sorafenib and sunitinib have shown promise in several clinical trials [7]. Because RCC is not uncommon in HNPCC, it would be reasonable to consider a preoperative angiogram to assess whether preoperative embolization of tumor feeders may decrease the risk of tumor cavity bleeding post tumor resection.…”
Section: Discussionmentioning
confidence: 99%